Knowledge of the mothers of hospitalized children in a university hospital regarding diarrhea - Ana Paula do Rego; Simone Pedrosa Lima; Maria Cláudia Medeiros Dantas de Rubim Costa; Lauriana Medeiros Costa Santos; Wilton Rodrigues Medeiros; Eliane Santos Cavalcante (Rev Rene)
This qualitative research aimed at identifying the knowledge of the mothers regarding diarrhea. It was conducted with eight mothers of hospitalized children in a university hospital located in Santa Cruz, Rio Grande do Norte, Brazil, in 2012. Data were collected through open interviews and the analysis was based on Bardin. The categories emerging from the analysis were: understanding diarrhea and preventing/treating diarrhea. Regarding the understanding of diarrhea, mothers conceptualize and understand it from the symptoms, habits/eating mistakes and/or cultural beliefs. Concerning the prevention and treatment of the disease, the mothers highlight hygiene and home cleaning as preventive measures, as well the importance of home and hospital care measures. The interviewees have basic knowledge of pathology, further studies are necessary in order to define the current gap between the knowledge of mothers and recurrence of diarrhea cases, resulting in hospitalization and expenses with unnecessary treatment.